PRODUCTION OF KK-BAR-PAIRS IN PHOTON PHOTON COLLISIONS AND THE EXCITATION OF THE TENSOR MESON F'(1515) - Althoff, M; Brandelik, R; Braunschweig, W; Gather, K; Kirschfink, F; Lubelsmeyer, K; Martyn, H; Peise, G; Rimkus, J; Sander, H; Schmitz, D; Siebke, H; et al. (1983)
We have observed exclusive production of K+K- and KSOKSO pairs and the excitation of the f′(1515) tensor meson in photon-photon collisions. Assuming the f′ to be production in a helicity 2 state, we determine Λ(f′ → γγ) B(f′ → KK) = 0.11 ± 0.02 ± 0.04 keV. The non-strange quark of the f′ is found to be less than 3% (95% CL). For the θ(1640) we derive an upper limit for the product Λ(θ rarr; γγ KK) < 0.03 keV (95% CL). © 1983.